Functional capacity, etiology and anatomic injury in local stroke - Souza, Natália Rosa e; Caldeira, Luis Paulo; de Almeida Neto, Omar Pereira; Pereira, Maria Elizabeth Roza (Journal of Health Care, 2016)
Background: Despite technological and cerebrovascular scientific advances, stroke is still synonymous with mortality and functional disability. Objectives: To describe the clinical and socioeconomic profile and the functional capacity of post-stroke patients , as well as the type and anatomical site of involvement. Methods: Crosssectional, quantitative and descriptive study, held in AVC Clinic of the Federal University of Uberlândia. After the consent of the participants were conducted clinical and sociodemographic interviews and application of the National Institutes of Health Stroke Scale and the Barthel Index Modified.This study was approved by the ethics committee of the institution under no. 277,825. Results: We recruited 14 patients. The most prevalent type of stroke was hemorrhagic (64.28%), affecting the frontal lobe (42.85%), followed by the parietal lobe (28.59%). Most individuals were independent to get around (64.28%), but having difficulty performing activities of daily living (78.57%). The National Institutes of Health Stroke Scale showed moderate involvement (57.14%). Conclusion: The relationship between stroke hemorrhagic type and the functional capacity relates to more severe neurological deficits in regions such as the frontal and parietal brain lobes.
Keywords: stroke; neurologic manifestations; sequels and disability statistics.